Age Related Macular Degeneration Associated with Depression - Fadel Askary (Sriwijaya Journal of Ophthalmology, 2021)
AMD is a complex and multifactorial disease with factors such as age, lifestyle, ethnicity, and genetics all having an important role in modifying the onset, development and severity of sad disease. AMD is the leading etiology of non-reversible blindness in the older age population especially over 65 years old in developed country. It accounts for roughly 9% of worldwide blindness. Some studies have showed the poor visual acuity related to the presence of AMD was associated with depression. AMD and other degeneration problem of the eye contribute major psychologic problems, especially emotional distress and social isolation in older people. The potential development of depression and anxiety mechanisms among patients with vision loss have been suggested. First, a strong relationship comes between the impairment of functional capacity and depression symptoms. The second is the main problemsolving skill deficits. And the third, the speculation about differences the therapy control strategies of AMD can affect the depression symptoms. Future study should be benefit from clearly specifying the type of AMD, including a control or comparator group to allow for comparison of the prevalence depression between AMD and non-AMD populations, and the use of tools which give a clear cut-off for clinical depression.